Feminism as life's work : four modern American women through two world wars - Trigg, Mary K., 1955- (Rutgers University Press, 2014)
Tracing the intertwined lives and work of four women who carried forward the cause of feminism after the suffrage victory in 1920, this book recasts the "doldrums" of the women's movement as a time of experimentation in new realms-the National Women's Party; sexuality, marriage, and relations with men; and work and financial independence-and documents struggles that prefigure those of a later generation.